Unveiling the influences of prenatal and maternal factors on the journey of an autistic child - Abdelkader, Ahmed; AlRadini, Faten; Alosaimi, Ashwaq; Abbas, Abdallah; Judeh, Zaki; Emy Abu Esaid, Tahneed; Saleh, Alaa; Shah, Jaffer; Amer, Samar (Frontiers in Psychiatry, 2024)
BackgroundAutism Spectrum Disorder (ASD) is a complex lifelong neurodevelopmental disorder with a high and increasing global prevalence. Although the precise causes are unknown, both genetic and environmental factors, including maternal ones during pregnancy, significantly influence its development. Therefore, this study endeavors to explore the potential causes of autism, including maternal and paternal prenatal risk factors, as well as antenatal and natal maternal risk factors, and their associations with the severity of ASD in mothers of children with ASD, from February to May 2024.MethodsAt an autism center in Saudi Arabia, this cross-sectional study enrolled 168 mothers of children diagnosed with ASD. The web-based survey employs a structured questionnaire to gather comprehensive prenatal, natal, and demographic data. The collected data was coded and analyzed using suitable tests.ResultsThe majority of the surveyed 168 mothers with autistic children reported having autism spectrum disorder (43.8%), moderate autism (31.9%), mild autism (15.6%), and severe autism (8.8%). Most autistic children had a history of one or both maternal and/or paternal antenatal exposures: 79.2% had soft drink consumption, 35.1% smoked, 24.4% had chronic physical diseases, and 20.8% had psychological disease. Regarding maternal antenatal conditions, 37% had a history of recurrent infection, 29.2% had anemia, 15.5% had a history of threatened abortion or bleeding, as well as exposure to air pollution, and 22 (13.1%) had a history of gestational diabetes. Significant (p <0.05) predictors of severe autism were gestational diabetes aOR 4.553 (95% CI: [1.518, 14.25], birth oxygen desaturation 4.142 (95% CI: [1.437, 12.45]. Furthermore, the likelihood of classifying a child’s ASD as severe increases by 7.1% with each year of age1.071 (95% CI: [1.002, 1.15].ConclusionASD is a prevalent health condition that has many interrelationships with prenatal, maternal (medical, environmental, and psychosocial factors), and natal conditions. Prospective studies are essential for understanding and addressing these ASD risk factors.